Green Downstream Processing By Using Hydrothermal Extraction For Recovering Flavonoid, Phenolic And Antioxidant Activity From Moringa Oleifera Leaves - Ghusrina Prihandini; Paqih Purnama Alam (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
Well known as rich in phenolic compounds, Moringa oleifera mature leaf extract show significant antioxidant activity both in vitro and in vivo. It has been widely used at cosmetic, medicine, and functional food sector. Hydrothermal extraction, one of the green environmentally friendly method that fit to M. oleifera feedstock for recovering natural antioxidant namely flavonoid, phenolic, and antioxidant activity. Three parameters were used at this study such as sample-solvent ratio, running temperature and extraction time. Flavonoids were evaluated with 2.4 Dinitrophenyl hydrazine colorimetric, whereas phenolics were measured by tanat acid which react with Foulin ciocealteu reagent. Antioxidant activity was measured by DPPH. The optimum result was obtained at 15 minutes with 140 0C for total flavonoid content (TFC) 18.98 mg/g whereas 170 0C for total phenolic content (TPC) and antioxidant activity 48.73 mg tanat acid/dried extract; 44.76 mg/L respectively